SISTEM TANAM PADI JAJAR LEGOWO TUMPANGSARI DENGAN KACANG PANJANG SEBAGAI ALTERNATIF PENINGKATAN PRODUKTIVITAS DAN PENDAPATAN USAHATANI DI LAHAN SAWAH - I Ketut Arnawa; I Wayan Runa; I Made Sukerta; I Made Suryana; Putu Sri Astuti; Luh Kadek Budi Martini; I Dewa Nyoman Raka (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2017)
The purpose of this study is to know the knowledge of farmers about jajar legowo planting system, the income of rice jajar legowo planting system, the productivity of rice jajar legowo planting system and the efficiency of rice jajar legowo planting system. The research was conducted in Subak Paang Kelurahan Penatih, the method used was extension method, survey and experiment. To know the impact of the application of jajar legowo planting system to increase income and productivity of rice farming, compared with unlived of rice jajar legowo planting system, to know the efficiency of rice usagei used R / C. The result of the research found (1) farmers almost half of them or 45% to know about the technology of jajar legowo planting system (2) revenues of rice farming with jajar legowo planting system increased by Rp 7,446,250 / land area or 40.22%; (3) productivity of rice farming with jajar legowo planting system can increase 2,225 kg / land area or 28,80% and (4) rice farming system of jajar legowo planting system more efficient than without jajar legowo planting system.